Phosphorous determination in biochar-based fertilizers by spark discharge-laser-induced breakdown spectroscopy - Dib, Samia Rodrigues [UNESP]; Senesi, Giorgio Saverio; Neto, Jose Anchieta Gomes [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Ferreira, Edilene Cristina [UNESP] (MDPI, 2021)
Biochar-based fertilizers are a new attractive alternative to P supplementation for crops, as they can gradually release the nutrient, avoiding losses and improving soil quality. In this re-gard, the evaluation of the P amount in biochar-based fertilizers is extremely important for their quality control. Analytical techniques that require sample solubilization are not very efficient for this task, as biochar is difficult to solubilize. Laser-induced breakdown spectroscopy (LIBS) is a promising technique to respond to this demand, as it enables a direct analysis of solid samples, avoiding the complicated process of sample solubilization. In this work, a novel method based on spark discharge (SD) coupled to LIBS was evaluated for P determination in biochar-based fertilizers prepared from three different biomasses. To overcome calibration problems in LIBS analysis, a matrix-matching procedure accomplished by the addition of eucalyptus biochar to calibration standards was used in experiments. This procedure minimized matrix effects and allowed us to achieve a satisfactory accuracy even when applied to similar but different matrices. Furthermore, the developed method is simple, fast, direct, does not generate post-analysis residues and appears appropriate for the quality control of sustainable biochar-based fertilizers and other biochar products.
Keywords: Biochar-based fertilizers; Matrix matching; P analysis; SD-LIBS